PENGARUH LOYALITAS DAN INTEGRITAS TERHADAP KEBIJAKAN PIMPINAN DI PT. QUANTUM TRAINING CENTRE MEDAN - Aribowo Aribowo; Adelina Lubis; Hesti Sabrina (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
The purpose of this study was to determine the effect of loyalty and in partially letting the leadership policy at PT. Quantum Training Centre Medan. As well as the influence of loyalty and integrity simultaneously on the leadership policies at PT. Quantum Training Centre Medan. The population in this study were permanent employees of PT. Quantum Training Centre Medan as many as 78 people. To obtain the data in the preparation of this paper, the authors use the instrument; documentary studies and interviews (interview), as well as a questionnaire ( questionnaire ). In analyzing the data using multiple linear regression, t test, F test and determination. Based on the results of the partial test (t test) it can be concluded that loyalty has a significant influence on the integrity. Whereas integrity does not have a significant influence on the leadership policy. Based on F test results can be concluded that the variables of loyality and integrity is jointly significant effect on leadership policy. R-square value obtained was 0.949 showed about 94.9% variable Y ( leadership policy ) can be explained by the variable work loyalty (X1) and variable integrity (X2). The remaining 5,1% is influenced by other variables.